Five-Year Incidence and Predictors for Pterygium in a Rural Community in China: The Yunnan Minority Eye Study. Issue 12 (December 2015) - Li, Lan; Zhong, Hua; Tian, Ermiao; Yu, Minbin; Yuan, Yuansheng; Yang, Wenyan; Wei, Tao; Cha, Xueping; Li, Xun; Li, Juanjuan; Su, Xiaodan; Pan, Chen-Wei
Abstract : Purpose: To determine the 5-year cumulative incidence of pterygium and its associated predictors in the Bai Chinese population in a rural community. Methods: This population-based study included 2133 subjects aged 50 years or older in 2010 and was repeated in 2015 with 1520 subjects (71.3%) participating in the follow-up examination. Participants with pterygium in either eye in 2010 were excluded from the analysis related to incidence. Anterior segment examination was performed without pupil dilation using a slit lamp, and pterygium was defined as a raised fleshy triangular fibrovascular tissue growth of the conjunctiva encroaching onto the clear cornea. Results: The 5-year cumulative incidence of pterygium was 6.8% [95% confidence interval (CI), 5.2–8.4] and was significantly higher in women compared with men (8.8% vs. 3.8%; P = 0.003). The age-specific incidence was 7.7%, 6.5%, and 5.6% in those aged 50–59, 60–69, 70 years, or older at the baseline, respectively. Outdoor occupation was the only predictor, which remained to be significantly associated with a higher incidence of pterygium in multivariate analysis (odds ratio = 2.52, 95% CI, 1.27–4.95). The predictive effect of outdoor occupation on incident pterygium was moderate with an area under the curve in the receiver operating characteristic analysis of 0.59 (95% CI, 0.53–0.66). Conclusions: The incidence of pterygium in this rural cohort was higher compared to a previous report in Chinese in urban areas. The findings are important for health policy makers to project future burden of pterygium and make proper decisions on health resource allocation.